1986
DOI: 10.1530/jrf.0.0780231
|View full text |Cite
|
Sign up to set email alerts
|

Effect of male presence and of photoperiod on the sexual maturation of the field vole (Microtus agrestis)

Abstract: Summary. The effect of mature males on the sexual development of young female and male field voles, reared in either long (stimulating) or short (inhibiting) photoperiods, was examined. Females reared in the presence of a mature male had a more advanced state of sexual maturation (as indicated by uterine weight) than did females reared in isolation from males, in long and short photoperiods (P < 0\m=.\01). No interaction between photoperiod and male presence was found. Augmented uterine growth occurred not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…As the field vole is an induced ovulator (Breed, 1967), the absence of corpora lutea in the ovaries is to be expected. As Spears & Clarke (1986) found that female field voles grew at a faster rate in long than in short photoperiods. There seems to be no consistent relationship between photoperiod and growth rate amongst other species.…”
Section: Discussionmentioning
confidence: 95%
“…As the field vole is an induced ovulator (Breed, 1967), the absence of corpora lutea in the ovaries is to be expected. As Spears & Clarke (1986) found that female field voles grew at a faster rate in long than in short photoperiods. There seems to be no consistent relationship between photoperiod and growth rate amongst other species.…”
Section: Discussionmentioning
confidence: 95%
“…Antral follicular development was accelerated in ovaries of females kept from birth in long as compared to short DLs. Accelerated reproductive maturation occurs in females of other photoperiodic rodent species (Imel and Amann, 1979;Garcia and Whitsett, 1983;Spears and Clarke, 1986). Surprisingly, none of the individually housed long-day females had ovulated by 60 days of age, even though females housed with males not only ovulated but also conceived young as early as 37 days of age.…”
Section: Discussionmentioning
confidence: 99%
“…The onset of sexual maturation in female mammals can be influenced by environmental and social factors (Drickamer 1974, Hasler & Banks 1975, Teague & Bradley 1978, Spears & Clarke 1986, vom Saal 1989. The presence of adult conspecifics (Vandenbergh 1967(Vandenbergh , 1976, hormonal exposure during gestation (Zehr et al 2001) and diet (Whitten & Naftolin 1992, Thigpen et al 2003, Takashima-Sasaki et al 2006) have all been found to influence the timing of sexual maturity.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to adult males can induce early onset of sexual maturation in juvenile females of several mammals including mice (Vandenbergh 1967), rats (Vandenbergh 1976), lemmings (Hasler & Banks 1975), deer mice (Teague & Bradley 1978), voles (Spears & Clarke 1986), opossums (Harder & Jackson 2003) and cattle (Roberson et al 1991), a phenomenon often called the Vandenbergh effect. Within 24 h of male presence, juvenile females begin to show changes in uterine growth followed by surges in serum luteinizing hormone and follicle-stimulating hormone by the third day (Bronson & Stetson 1973).…”
Section: Introductionmentioning
confidence: 99%